Establishment of simultaneous analysis validation for Perilla frutescens var. acuta extract - JEON, So-Heon; CHOI, Hyo-Seung; Yim, Soon-Ho (Food Science and Technology, 2023)
In this study, the UV spectra maximum absorption wavelengths and molecular weights of major compounds 1–3 were identified in Perilla frutescens var. acuta extract using high-performance liquid chromatography (HPLC)-DAD and HPLC-MS/MS. Luteolin-7-O-diglucuronide (1), scutellarin (2), and rosmarinic acid (3) were identified, and simultaneous analysis validation was performed for quantification using HPLC-DAD. All linearities showed R2 values of 0.9993 or higher, and the limits of detection and quantification were measured in the ranges of 4.4802–5.4133 and 13.5764–16.4038 µg/mL, respectively. The relative standard deviation (RSD) values for accuracy ranged from 0.09 to 0.89%, and the recovery rates were in the range of 99.36–101.96%. The precision RSD values within the laboratory were in the range of 0.05–1.04%, and the RSD values for repeatability evaluation were below the guideline criteria of 2%. The content change of the three marker compounds within 24 h was 0.36–0.69%, confirming the chemical stability of the extract within 24 h, which was below the guideline criteria of 2.0% established by the Ministry of Food and Drug Safety guidelines. The content analysis of the extract according to ethanol concentration showed that luteolin-7-O-diglucuronide had the highest content of 302.22 µg/mL in the 0% ethanol extract, while scutellarin and rosmarinic acid showed the highest contents of 103.61 and 118.77 µg/mL, respectively, in the 60% ethanol extract.